Cash flow prediction by gross profit, operating profit and net profit in Indonesian food and beverage companies - Abdul Hamid; Imas Dian Oktarini; Tri Wahjoedi (New Applied Studies in Management, Economics & Accounting, 2023)
The goal of this study is to forecast cash flow during the Covid-19 pandemic in food and beverage companies registered on the Indonesian stock exchange using gross profit, operational profit, and net profit. This study employs a sample of 18 businesses to make it quantifiable. SPSS version 26 was utilized for the analysis in this study. According to the study's findings, gross profit has a positive and significant impact on cash flow, operating profit and net profit do not, but gross profit, operating profit, and net profit all have an impact on cash flow simultaneously. It is clear that gross profit has the greatest impact on cash flow. This shows that the company's cash flow will increase along with its gross profit. This study provides input to enrich the theory about the relationship between cash flow and company profits.